2022
DOI: 10.3390/bios12110950
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Gated Mesoporous Silica Nanoparticles for N Protein Triggered Release of Remdesivir and Treatment of Novel Coronavirus (2019-nCoV)

Abstract: Since the 2019-nCoV outbreak was first reported, hundreds of millions of people all over the world have been infected. There is no doubt that improving the cure rate of 2019-nCoV is one of the most effective means to deal with the current serious epidemic. At present, Remdesivir (RDV) has been clinically proven to be effective in the treatment of SARS-CoV-2. However, the uncertain side effects make it important to reduce the use of drugs while ensuring the self-healing effect. We report an approach here with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In contrast, studies of SNPs carrying proteins or antiviral drugs for SARS-CoV-2 have been approved. For instance, Zhang’s group prepared MSNs carrying remdesivir for targeted drug delivery in vitro . Mizuta and colleagues developed hybrid SNPs and evaluated their antigen-carrying ability .…”
Section: Biomaterials Help To Anti-sars-cov-2 Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, studies of SNPs carrying proteins or antiviral drugs for SARS-CoV-2 have been approved. For instance, Zhang’s group prepared MSNs carrying remdesivir for targeted drug delivery in vitro . Mizuta and colleagues developed hybrid SNPs and evaluated their antigen-carrying ability .…”
Section: Biomaterials Help To Anti-sars-cov-2 Strategiesmentioning
confidence: 99%
“…For instance, Zhang’s group prepared MSNs carrying remdesivir for targeted drug delivery in vitro. 182 Mizuta and colleagues developed hybrid SNPs and evaluated their antigen-carrying ability. 183 Importantly, research based on biodegradable mesoporous silica nanoparticles (BMSNs) has demonstrated robust immunogenicity in vivo on high TH1-based humoral and cellular immune responses.…”
Section: Biomaterials Help To Anti-sars-cov-2 Strategiesmentioning
confidence: 99%